2021
DOI: 10.3389/fcell.2021.653812
|View full text |Cite
|
Sign up to set email alerts
|

ORAI1 Ca2+ Channel as a Therapeutic Target in Pathological Vascular Remodelling

Abstract: In the adult, vascular smooth muscle cells (VSMC) are normally physiologically quiescent, arranged circumferentially in one or more layers within blood vessel walls. Remodelling of native VSMC to a proliferative state for vascular development, adaptation or repair is driven by platelet-derived growth factor (PDGF). A key effector downstream of PDGF receptors is store-operated calcium entry (SOCE) mediated through the plasma membrane calcium ion channel, ORAI1, which is activated by the endoplasmic reticulum (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 223 publications
0
15
0
Order By: Relevance
“…Concerning inhibitors of Orai1, there is a well-known family of pyrazole derivatives, with the widely used BTP2 (YM-58483) [ 214 , 215 , 216 , 217 , 218 ] and GSK compounds (GSK7975A and GSK-5503A) [ 220 ], acting on the selectivity filter of Orai1, Synta-66, which binds directly to Orai1 [ 221 , 222 , 223 , 224 ] and its suitable in vivo analogue JPIII [ 225 ]. The lanthanide family (Gd 3+ or La 3+ ) has been known as an Orai blocker for many years [ 219 , 226 ].…”
Section: Targeted Soce In Pah: a Novel Therapeutic Option?mentioning
confidence: 99%
“…Concerning inhibitors of Orai1, there is a well-known family of pyrazole derivatives, with the widely used BTP2 (YM-58483) [ 214 , 215 , 216 , 217 , 218 ] and GSK compounds (GSK7975A and GSK-5503A) [ 220 ], acting on the selectivity filter of Orai1, Synta-66, which binds directly to Orai1 [ 221 , 222 , 223 , 224 ] and its suitable in vivo analogue JPIII [ 225 ]. The lanthanide family (Gd 3+ or La 3+ ) has been known as an Orai blocker for many years [ 219 , 226 ].…”
Section: Targeted Soce In Pah: a Novel Therapeutic Option?mentioning
confidence: 99%
“…A separate study by Zhang et al showed that GSK7975A largely inhibits Orai1 and Orai2 while it has a lower inhibitory effect against Orai3 [ 72 ]. As GSK7975A is unable to discriminate between Orai1 and Orai3 channels, as well as lacking the ability to block L-type Ca 2+ and TRPV6 channels, the compound has a limited specificity as an Orai1 channel blocker [ 23 ].…”
Section: Pharmacology Of Store-operated Calcium Entry Channelsmentioning
confidence: 99%
“…Somatic cell migration and proliferation (SOCE) mediated by Orai1 are related with the stimulation of the nuclear factor of the activated T-cell (NFAT), which increases the proliferation and migration of VSMCs. Additionally, Ca 2+ influx through Orai1 stimulates mitochondrial Ca 2+ uptake through the mitochondrial Ca 2+ uniporter [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, molecular targets that do not, or only mildly affect bleeding times, are promising candidates for improved future anti-platelet and antithrombotic treatment regimens. While there is a plurality of SOCE interfering compounds which are well summarized by Shawer et al [ 113 ], only inhibitors of SOCE compounds described in platelets and thrombus formation are briefly described here.…”
Section: Implications For Potential Pharmacological Interventionsmentioning
confidence: 99%
“…Moreover, in vivo administration of SKF-96365 leads to a significantly reduced atherosclerotic plaque progression in a mouse model using apolipoprotein E knockout mice [ 120 ]. However, comparable with 2-APB, the effect of SKF-96365 on platelet function and atherothrombosis cannot be clearly linked with the SOCE machinery in platelets, since a lot of other ion channels are reported to be affect by SKF-96365 [ 113 ]. Amongst others, work by Derler and colleagues in 2013 identified GSK-7975 A as a pore-forming blocking compound of Orai-mediated SOCE [ 121 ].…”
Section: Implications For Potential Pharmacological Interventionsmentioning
confidence: 99%